Summer training camp decrease food intake in adolescent rugby football players - Nagayama, C.; Muto, K.; Iwami, M.; Ishihara, M.; Tobina, T. (Science & Sports, 2019)
Sufficient and well-balanced nutrients promote optimal athletic performance. This study investigated appetite and food intake in adolescent rugby football players before and during a summer training camp. Eleven male national-level athletes who took part in a 6-day camp participated in this study. To calculate their physical activity level, participants wore heart-rate monitors during simulated rugby game training and accelerometers at other times. All participants took photographs of the food they ate during camp. The meals provided in the dormitory were recorded with the weighed-food record method. Before and after the camp, an ad libitum buffet test was carried out to assess appetite. Although there was no significant difference between total energy expenditure and total energy intake during the camp (15730±1765 kJ·day-1 vs. 14838±1708 kJ·day-1, respectively), the mean energy deficit was -892±2,107 kJ·day-1 and 82% of participants had insufficient intake. Energy and carbohydrate intake in the buffet test were lower after camp than before (energy: 7122±1385kJ after vs. 8226±1329kJ before, P<0.05; carbohydrates: 250±47g after vs. 297±40g before, P<0.05). Over the 6-days of a summer training camp, adolescent male national-level rugby football players were in a negative energy balance and had insufficient carbohydrate intake. Additionally, rugby plays decreased energy and carbohydrate intake at ad libitum buffet meals at the end of camp.